Health Education on the Prevention of Post Partum Depression at the Bara-Baraya Health Center, Makassar City - Firawati, Firawati; Hasnita, Hasnita (Lembaga Riset dan Inovasi Masyarakat Madani, 2023)
Postnatal depression is a disorder that occurs in mothers after giving birth. This disorder occurs in her mood, this condition can cause the mother to be easily sad, tired, irritable, cry for no apparent reason, easily anxious and have difficulty concentrating. The worst condition a mother can experience is when she hurts herself or even her baby. The aim of community service is to increase public knowledge about postnatal depression and how to prevent it. The method for organizing PKM is lectures/counseling, discussions and questions and answers with activities providing material related to postnatal depression and its prevention. This activity was attended by 26 participants who were postpartum mothers. Results: mothers were very enthusiastic and active in asking questions, the level of knowledge of postpartum mothers before being given education about postpartum depression was at sufficient knowledge and after being given education increased to high to good knowledge. Health education regarding the prevention of postnatal depression in postpartum mothers needs to be carried out continuously in order to reduce the incidence of postnatal depression and requires the role and support of husbands to provide special attention to reduce the incidence. from postpartum depression.